Drama, idyll og eventyr: Gunnar Sommerfeldts filmadaptasjon (1921) av Hamsuns «Markens grøde» - Wærp, Lisbeth P. (Nordlit, 2016)
This article examines Gunnar Sommerfeldt’s 1921 silent movie adaptation of Knut Hamsun’s Nobel Prize novel Markens grøde [Growth of the Soil] (1917). The article argues that what characterizes this very first Hamsun film adaptation is its emphasis on the dramatic and the spectacular and its foregrounding of northern Norwegian nature. Inspired by Martin Lefebvre’s distinction in Landscape and Film (2006) between nature-as-setting and nature-as-landscape, this article argues that the film not only uses nature as its main setting, but that it also makes use of a series of autonomous landscapes with a fairy tale dimension. Several of its visual compositions of persons and landscapes seem to be inspired by Norwegian nature and fairy tale painter Theodor Kittelsen’s work, e.g. Soria Moria Slott, Nøkken, Pesta and Norge, Norge.